2022
DOI: 10.1371/journal.pcbi.1009855
|View full text |Cite
|
Sign up to set email alerts
|

Chiral evasion and stereospecific antifolate resistance in Staphylococcus aureus

Abstract: Antimicrobial resistance presents a significant health care crisis. The mutation F98Y in Staphylococcus aureus dihydrofolate reductase (SaDHFR) confers resistance to the clinically important antifolate trimethoprim (TMP). Propargyl-linked antifolates (PLAs), next generation DHFR inhibitors, are much more resilient than TMP against this F98Y variant, yet this F98Y substitution still reduces efficacy of these agents. Surprisingly, differences in the enantiomeric configuration at the stereogenic center of PLAs in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…While the concept that different enantiomers may have different biological activity is well-known, very recently Donald and co-authors observed that a single mutation (F98Y) in the methicillin-resistant Staphylococcus aureus flips the enantio-preference for cofactor binding and induces stereospecificity for binding of propargyl-linked antifolates as an antimicrobial drug . In this study, the bacterial enzyme target was found to evade inhibitor binding stereoselectively ( chiral evasion ).…”
Section: Trends In Enantioselective Recognition In Natural and Synthe...mentioning
confidence: 99%
“…While the concept that different enantiomers may have different biological activity is well-known, very recently Donald and co-authors observed that a single mutation (F98Y) in the methicillin-resistant Staphylococcus aureus flips the enantio-preference for cofactor binding and induces stereospecificity for binding of propargyl-linked antifolates as an antimicrobial drug . In this study, the bacterial enzyme target was found to evade inhibitor binding stereoselectively ( chiral evasion ).…”
Section: Trends In Enantioselective Recognition In Natural and Synthe...mentioning
confidence: 99%
“…While the cut-off for resolution is still a matter of discussion in the scientific community, previous successful designs have used X-Ray diffraction resolutions ranging between 1.4 and 3.15 Å. 6 , 7 , 16 , 17 , 18 We have also had success with cryo-EM resolutions between 3.4 and 11.5 Å. For NMR structures, we recommend that the structure determination use RDCs; 2.…”
Section: Before You Beginmentioning
confidence: 99%
“…In cases where empirical structures are not available, it is possible to use docking, homology modeling, or other computational modeling techniques to generate structures. 1 , 6 , 7 , 17 , 20 For example, computational tools such as Modeller 21 or Alphafold 22 could be used to predict an initial protein structure, and docking tools such as AutoDock Vina 23 or those included in Maestro 19 could be used to dock the positive and negative design ligands. 1 , 3 With the recent explosion of available structural models, such as the Alphafold Protein Structure Database, 24 it may even be the case that a computationally predicted starting structure already exists.…”
Section: Before You Beginmentioning
confidence: 99%
“…SMX is a specific inhibitor of the dihydropteroate synthesis (DHPS) enzyme. It has been reported that the Phe98 group in DHFR is mutated to Tyr (F98Y) in many pathogenic S. aureus variants (Wang et al, 2022). Staphylococcus aureus with mutated DHFR developed resistance to the diaminopyrimidine (DAP) ring of TMP.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying compounds different from TMP and those that are devoid of the DAP ring would help develop new therapeutic agents for patients infected with TMP-resistant S. aureus strains, as well as MRSA, VRSA, and caMRSA strains (Holland et al, 2014). Drug discovery targeting TMP-resistant S. aureus DHFR (TMP-resistant saDHFR) has attracted a great deal of attention (Huang et al, 2019;Keshipeddy et al, 2015;Reeve et al, 2019;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%